2013
DOI: 10.1016/j.cyto.2013.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine synergy: An underappreciated contributor to innate anti-viral immunity

Abstract: Inflammatory cytokines, such as tumor necrosis factor and the members of the interferon family, are potent mediators of the innate anti-viral immune response. The intracellular anti-viral states resulting from treatment of cultured cells with each of these molecules independently has been well studied; but, within complex tissues, the early inflammatory response is likely mediated by simultaneously expressed mixures of these, and other, protective anti-viral cytokines. Such cytokine mixtures have been shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 40 publications
0
50
0
Order By: Relevance
“…As RNA expression of the signaling intermediary Myd88, a fundamental component of the TLR signaling pathway, 51,52 was, like STAT1, attenuated in cells lacking constitutive IFNb signaling, it is plausible that tonic IFNa/ b augments TLR responsiveness by regulating the expression of Myd88. Moreover, as expression or activation of transcription factors involved in signaling via other cytokines known to engage in crosstalk with IFNa/b such as IL-6, IL-1 and TNFa 6,27,28,[53][54][55] were also revealed by our studies to be attenuated in IFNAR1-deficient cells, it suggest that tonic IFNa/b also regulates responsiveness to these cytokines by this mechanism.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…As RNA expression of the signaling intermediary Myd88, a fundamental component of the TLR signaling pathway, 51,52 was, like STAT1, attenuated in cells lacking constitutive IFNb signaling, it is plausible that tonic IFNa/ b augments TLR responsiveness by regulating the expression of Myd88. Moreover, as expression or activation of transcription factors involved in signaling via other cytokines known to engage in crosstalk with IFNa/b such as IL-6, IL-1 and TNFa 6,27,28,[53][54][55] were also revealed by our studies to be attenuated in IFNAR1-deficient cells, it suggest that tonic IFNa/b also regulates responsiveness to these cytokines by this mechanism.…”
Section: Discussionmentioning
confidence: 74%
“…In contrast, the physiological scenario of concomitant exposure to several cytokines and the consequences and mechanisms regulating these interactions are relatively undefined. 28 Cytokine crosstalk can occur at the level of the receptor, by regulation of the expression of receptor components or the e1173804- 8 Messina et al…”
Section: Discussionmentioning
confidence: 99%
“…While TNFα is reported to potentiate the antiviral effects of IFNs against an array of DNA and RNA viruses 15, 17, 38 , the mechanisms behind such activities are not well understood. It has been proposed that TNFα acts in part by inducing expression of IFNβ in some cell types (reviewed in 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…TNFα can mediate antiviral activities by itself 15, 16 and in synergy with IFNs (reviewed in 17 ). In hepatocytes, TNFα was reported to inhibit hepatitis B virus (HBV) gene expression and replication, and to synergize with IFNγ 18–20 .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, intensive research efforts have been focused on key cytokines such as IL-1, IL-6, IL-12 and IL-17 and the targeting of these molecules therapeutically in a variety of inflammatory and autoimmune diseases [15,48]. It is being increasingly recognized that cytokines do not act in isolation, but function within a milieu of multiple cytokines with the ability to synergize with or antagonize one another's functional capacity [47,51]. For example, in-vitro studies examining the combined effects of TNF-α, IL-1β and IL-17 demonstrated enhanced activation of inflammatory signalling pathways in comparison to the individual cytokines alone.…”
Section: Current Concepts In Cytokine Functioningmentioning
confidence: 99%